Dorastanie bezprzewodowe. Technologie mobilne i gender w rodzinnym polu socjalizacyjnym = Wireless adolescence: mobile technologies and gender in the arena of family socialization - Kopciewicz, Lucyna (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The aim of this text is to present some selected excerpts of video-ethnographic research dedicated to "wireless adolescence": socialization and learning in the family environment. However, the core of the text is not to present ("report") the results of research, but rather to respond to the ways of constructing mobile technologies (and designing their use) by adults and children in the context of home socialization and in the culturaltechnological conduct of constructing gender (understood as collection of positions, points of view and activities accepted/undertaken in relation to mobile technologies).
Keywords: technologie mobilne; socjalizacja; płeć; adolescencja; mobile technologies; socialization; gender; adolescence